Biomass‐Derived Catalysts for Selective Hydrogenation of Nitroarenes. Issue 15 (17th July 2017) - Sahoo, Basudev; Formenti, Dario; Topf, Christoph; Bachmann, Stephan; Scalone, Michelangelo; Junge, Kathrin; Beller, Matthias
Abstract: Development of catalytically active materials from biowaste represents an important aspect of sustainable chemical research. Three heterogeneous materials were synthesized from inexpensive biomass‐based chitosan and abundant Co(OAc)2 using complexation followed by pyrolysis at various temperatures. These materials were applied in the catalytic hydrogenation of nitroarenes using molecular hydrogen. A variety of diversely functionalized nitroarenes including some pharmaceutically active compounds were converted into aromatic amines in high yields, with high selectivity, and with excellent functional group tolerance. This green protocol has also been implemented for the synthesis of a biologically important TRPC3 inhibitor. Abstract : Shelling out for a shrimpy catalyst : Biowaste represents an important source of sustainable chemical precursors. Three heterogeneous catalysts were synthesized from inexpensive chitosan and abundant Co(OAc)2 followed by pyrolysis at various temperatures. The materials were used for the effective and selective hydrogenation of nitroarenes, including some pharmaceutically active compounds.